Phase separation during the topotactic reduction of the pyrochlore Y2Ti2O7 - Hayward, M (2005)
The topotactic reduction of the pyrochlore Y2Ti 2O7 with CaH2 is described. Neutron and X-ray powder diffraction data reveal the reduction yields mixtures of two reduced phases: Y2Ti2O6.48(2), a material from which oxide ions have been removed from the 48f anion site, and Y2Ti 2O5.90(6), which exhibits a small amount of cation antisite disorder and a complicated defect anion structure. An electronic origin for the observed phase separation is explored. Magnetic data collected from reduced samples are consistent with delocalized metallic behavior.